Effect of Paclobutrazol, Pluronic-F 68 and Phloroglucinol on Micropropagation of Aloe vera - Saroha, V.; Yadav N.R.; Yadav, R.C.
Aloe vera, an important medicinal plant of Liliaceae family, is known as 'wand of heaven' or 'doctor in a pot' as it has more than 200 nutrients which are used in curing different diseases. Indian government is promoting Aloe farming in dry and semi dry areas of India as it requires less water for its growth. Micropropagation is an effective way to provide quality planting material as conventional methods are slow and labor intensive. Sterilized vertical sections were dissected and cultured on MS medium with 2 mg/L BA and 0.18 mg/L IAA. Shoot initiation started in 12 days. Multiple shoots (8-12 per explant)were observed, which were separated and cultured on six different media including NAA (0.1 mg/L), IBA (0.1 mg/L), IAA (0.1 mg/L), 1.0 mg/L phloroglucinol, 1.0 mg/L pluronic-F 68 and 0.5 mg/L paclobutrazol. It was observed that paclobutrazol enhanced rooting in Aloe vera shoot cultures. Around 12 healthy roots measuring nine cm long were observed in paclobutrazol medium whereas in pluronic- F68 containing medium, maximum of 4 roots per shoot of average 8 cm length obtained. Phloroglucinol medium exhibited three roots per shoot of average 4 cm length. Interestingly on paclobutrazol we obtained shoots with thin skinned fleshy leaves of light green color with high gel quantity of as compared to plants regenerated in other media and field grown plants. These plants showed more number of offshoots when planted in soil.
Keywords: MEDICINAL PLANT; SHOOT INDUCTION; SHOOT ELONGATION; ROOTING MEDIUM; COMMERCIAL PRODUCTION